Predictors of COVID-19 vaccine acceptability among refugees and other migrant populations: A systematic scoping review. - Yasaman Yazdani; Poojitha Pai; Shahab Sayfi; Arash Mohammadi; Saber Perdes; Denise Spitzer; Gabriel E Fabreau; Kevin Pottie (PLoS ONE)
Objective This study aimed to map the existing literature to identify predictors of COVID-19 vaccine acceptability among refugees, immigrants, and other migrant populations. Methods A systematic search of Medline, Embase, Scopus, APA PsycInfo and Cumulative Index of Nursing and Allied Health Literature (CINAHL) was conducted up to 31 January 2023 to identify the relevant English peer-reviewed observational studies. Two independent reviewers screened abstracts, selected studies, and extracted data. Results We identified 34 cross-sectional studies, primarily conducted in high income countries (76%). Lower vaccine acceptance was associated with mistrust in the host countries' government and healthcare system, concerns about the safety and effectiveness of COVID-19 vaccines, limited knowledge of COVID-19 infection and vaccines, lower COVID-19 risk perception, and lower integration level in the host country. Female gender, younger age, lower education level, and being single were associated with lower vaccine acceptance in most studies. Additionally, sources of information about COVID-19 and vaccines and previous history of COVID-19 infection, also influence vaccine acceptance. Vaccine acceptability towards COVID-19 booster doses and various vaccine brands were not adequately studied. Conclusions Vaccine hesitancy and a lack of trust in COVID-19 vaccines have become significant public health concerns within migrant populations. These findings may help in providing information for current and future vaccine outreach strategies among migrant populations.